Specific Viruses Detected in Nigerian Children in Association with Acute Respiratory Disease - Oluwabukola M. Akinloye; Esa Rönkkö; Carita Savolainen-Kopra; Thedi Ziegler; Bamidele A. Iwalokun; Mope A. Deji-Agboola; Afolabi Oluwadun; Merja Roivainen; Festus D. Adu; Tapani Hovi (Journal of Tropical Medicine)
Occurrence of different viruses in acute respiratory tract infections of Nigerian children was examined. Respiratory swabs were collected from 246 children referred to hospital clinics because of acute respiratory symptoms from February through May 2009. Validated real-time RT-PCR techniques revealed nucleic acids of at least one virus group in 189 specimens (77%). Human rhinoviruses and parainfluenza viruses were present each in one third of the children. Adenoviruses, enteroviruses, human metapneumovirus, human bocavirus, and influenza C virus were also relatively common. Possibly due to their seasonal occurrence, influenza A and B virus, and respiratory syncytial virus were detected rarely. We conclude that all major groups of respiratory tract viruses are causing illness in Nigerian children.